Incidental Development of Pronunciation Learning Strategies - Jarosz, Anna (Research in Language, 2021)
The studies devoted to the so-called good language learners that emerged in the 1970s (Rubin 1975) reveal that efficient learners fall back on an abundant and highly individualised array of techniques and strategic behaviours related to and employed while learning. The well-known taxonomies by Oxford (1990) and O’Malley and Chamot (1990) gave rise to analyses and investigations in the field of learner autonomy and self-development, also in pronunciation learning/teaching. As has been corroborated by empirical studies (Oxford 2001a; Oxford 2001b; Chamot, 2004) strategy training contributes to the increase in overall proficiency as well as to a number of invaluable benefits such as enhanced motivation, greater self-efficacy, anxiety reduction and more positive attitudes. Although studies dedicated to the relationship between learning strategies and pronunciation are still in their infancy, there are a number of investigations that set the directions for further research and development (Peterson 2000; Pawlak 2008; Pawlak and Oxford 2018).The paper presents results of a pilot study conducted in a secondary school that aimed at observing how learners develop pronunciation strategies as a result of regular pronunciation input and feedback from the teacher. It addresses a tentative assumption that explicit pronunciation training may contribute to the enhanced strategy use and consequently to better oral performance. Detecting and naming the strategies employed by the learners as well as selecting the most effective ones for more explicit application aided and boosted the learners’ awareness and confidence, which was confirmed by data obtained from questionnaires and from participant observation.